PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS X SMK BISNIS DAN TEKNOLOGI BEKASI - Maulana Panji; Yayat Suharyat (Turats, 2023)
This study aims to determine the quality of spiritual intelligence of class X students of SMK Business and Technology Bekasi, to find out how the quality of learning achievement of Islamic Religious Education students of class X SMK Business and Technology Bekasi. And to find out the relationship between spiritual intelligence and learning achievement of Islamic Religious Education class X SMK Business and Technology Bekasi. This research is a quantitative research using the correlation method. The population in this study were students with a sample based on proportional random sampling technique. The formula used is the Slovin formula and obtained a number of 74 students. The results showed that there was a significant relationship between spiritual intelligence and learning achievement in Islamic education. This is known through the acquisition of the Pearson correlation results obtained with a significant value = 0.029 which means a significant value < (0.10) so that H0 is rejected and H1 is accepted.